Survei Angka Kejadian Dermatitis Kontak Pada Pekerja Yang Berobat Di Klinik Pabrik Semen Bosowa Periode Tahun 2020-2022 - Muthmainnah , Annisaa Dwi; Nurliana, Nurliana; Naiem, M Furqaan (Bosowa Medical Journal, 2023)
The incidence of contact dermatitis among industrial workers is quite high. Regarding data on skin diseases in workers, most (90%) are in the form of allergic contact dermatitis and irritant contact dermatitis. Contact dermatitis is skin inflammation as a skin response to exogenous and endogenous factors that cause clinical abnormalities in the form of polymorphic efflorescence and itching complaints. The purpose of this study was to determine the incidence of contact dermatitis in workers seeking treatment at the Bosowa cement factory clinic for the period 2020-2022 based on age, gender, years of service and work unit. This research is a retrospective descriptive study, that describes the incidence of contact dermatitis in workers by reviewing the medical records of workers who sought treatment at the Bosowa cement factory clinic for the period 2020-2022. All workers diagnosed with contact dermatitis during the 2020-2022 period became the study sample (total sampling). The results of this study show that there will be 131 workers with contact dermatitis in 2020-2022. The most sufferers by age group were aged 36-45 years, namely 67 people (51.1%), according to gender were men, namely 106 people (80.9%), according to years of service. the highest was the group of years of service 17-22 years, namely 44 sufferers (33.6%), and according to the work unit, the most sufferers were in the production and mining sections, namely 37 people (28.2%) each